1990
DOI: 10.1302/0301-620x.72b2.2312556
|View full text |Cite
|
Sign up to set email alerts
|

Cementless total replacement for severely dysplastic or dislocated hips

Abstract: We report the short-term results of 100 cementless total hip replacements in 52 severely dysplastic and 48 totally dislocated hips, with some new technical solutions to the problems involved. In cases with a very narrow iliac bone, the acetabular screw ring is seated below the true cotyloid area. In hips with tight flexor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
13

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 20 publications
3
113
0
13
Order By: Relevance
“…His outcome was a stable hip but at the expense of limitation of movement. Lai Liu & Liu [16] have shown good results with Wagner tibiofemoral distraction followed by total hip replacement in [17] congenitally dislocated hips. Irreducibility, over shortening, nerve palsy, dislocation and femoral fractures were avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…His outcome was a stable hip but at the expense of limitation of movement. Lai Liu & Liu [16] have shown good results with Wagner tibiofemoral distraction followed by total hip replacement in [17] congenitally dislocated hips. Irreducibility, over shortening, nerve palsy, dislocation and femoral fractures were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the chronically dislocated hip is controversial with most studies focusing on congenital dislocation and dysplastic hips. Femoral shortening, either by metaphyseal resection or subtrochanteric osteotomy, trochanteric osteotomy with distal advancement and soft-tissue release has been advocated [17,19,20]. These procedures are technically demanding and need careful study of the anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…In tum, these serve as prerequisites for the final consolidation of the graft. (Stamos 1984, Paavilainen 1990, Young 1991, Rodriguez 1995 True consolidation and remodeling of the bulky Acta Orthop Scand (Suppl 275) 1997;68: 33-37 corticocancellous grafts is still controversial. In one report with 2 necropsies in which 2 deep freezed autologous bone grafts had been used, the findings indicated that true consolidation and healing of the graft had not occurred (Hooten 1996).…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, however, a growing number of articles have reported successful management of these difficult hips using total hip arthroplasty, the most of which are cemented (Paavilainen et al 1990, Hartofilakidis et al 1996.…”
Section: Bone Grafting In Total Hip Arthroplasty For Insufficient Acementioning
confidence: 99%
“…During 1982-1986, we treated 100 severely dysplastic or dislocated hips with uncemented Lord arthroplasties and reported the outcome (Paavilainen et al 1990). The main principles of the osteoplasties we use today were developed on basis of this work.…”
Section: Outcome Of a Previous Seriesmentioning
confidence: 99%